PENGARUH KONSENTRASI GIBERELIN TERHADAP PRODUKSI BIBIT KENTANG (SOLANUM TUBEROSUM L. CV. GRANOLA) UKURAN M (31 - 60 GRAM) - Arpiwi, Ni Luh (Jurnal Biologi Udayana; Vol XI, No 1, 2007)
The aim of the research was to increase the production of seed potato size 31 - 60 grams by applying gibberellic acid (GA3). Seeds that passed their dormancy period were dipped in gibberellic acid solutions (10, 15 and 20 mg/L) for 15 minutes a day before planting. Control seeds were dipped in water. Seeds were then air dried for 24 hours. Seeds were planted in plots with length, width and height of 150 x 100 x 30 cm respectively with planting space 20 cm and planting depth 15 cm. The design was randomized block with four replications. The results showed that gibberellic acid enhanced shoot emergence. Gibberellic acid increased stem number, tuber number and yield per plant. Tuber number and yield of size M (31 ? 60 g) increased, whereas tuber number and yield of size LL decreased drastically. The optimum concentration of gibberellin for these increases was 15 mg/L. Plant height was not influenced by gibberellic acid.
Keywords: production; seed potato; concentration; gibberellic acid